Surgical approaches in the treatment of patients with acute acetabular fractures - Nikolay V. Zagorodny (Russian Ilizarov Scientific Center for Restorative Traumatology and Orthopaedics, 2021)
Abstract. Introduction According to the overwhelming majority of Russian and foreign authors, orthopedic traumatologists have been striving to improve the results of surgical treatment of acetabular (AC) fractures over the past decades. First of all, this is due to an increase in the number and severity of this injury, persisting complications and dissatisfaction of researchers with their own results of surgical treatment. Purpose Study of the rationale used by traumatologists for certain surgical approaches in the treatment of acute acetabular fractures. Materials and methods Literature sources were searched for information in the systems and databases Pubmed, Embase, Scopus, Medline, Cochran Library, eLibrary, Wiley Online Library using the keywords: acetabular fractures, surgical treatment, acetabular approach, open reduction and fixation of acetabular fractures, duration and blood loss, hip arthroplasty. Results The incidence of AC fractures, according to different authors, ranges from 2 to 23.4 %. The cause of this injury is road traffic accidents in up to 83 % of all cases. A significant increase in the number of AC fractures was noted. AC fractures in the vast majority of cases are classified according to AO/ASIF. Displaced AC fractures and multiplanar fractures are subject to surgical treatment. Open reduction and internal fixation still remain the standard treatment for AC fractures. The choice of the surgical approach is carried out more often taking into account the classification of AC fractures, and the type of fracture dictates the choice of approach to the acetabulum. It was found that the authors are forced to use surgical approaches taking into account the fractures of the AC columns. Discussion Adherence of traumatologists to the standards regarding indications for the choice of surgical approaches for complex AC fractures was noted. Surgical approaches for the treatment of two-column acetabular fractures are still often extended and traumatic, prolonged and accompanied by blood loss. Conclusion In the surgical treatment of pelvic and AC fractures, most authors adhere to standards in the choice of approach and fixation of columns and AC fragments. There is unanimity in the recognition of the trauma and "expansion" of the approaches used, accompanied by blood loss reaching up to 2000 ml and more, and the duration of the operation is on average 3 hours 50 minutes. For the surgical treatment of acute AC fractures, the researchers used both classical and modified anterior and posterior surgical approaches with the obligatory consideration of the classification of AC fractures. The rationale for choosing an operative approach, as a rule, was the determination of the type of AC fracture according to the AO/ASIF classification. The most effective approach in the surgical treatment of AC fractures is the combined anterior and posterior approach.